ANALYTICAL HIERARCHY PROCESS IN CHOOSING MEN FACIAL SKIN CARE PRODUCTS. A STUDY OF PONDS, GARNIER AND NIVEA - Togubu, Siti Faya Ila; Saerang, David P.E; Worang, Frederik G. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: The purposes in this research are to determine which men facial skin care product that are chosen the most and which the criteria that are influence the most. This research used Analytical Hierarchy Process (AHP) to compare each facial skin care product based on the criteria; Price, Promotion, Avaiability, Quality, Packaging, Product Variety. This research held from August-September 2016 in Samratulangi University Manado. The respondent is 100 male students, this research using purposive sampling. The respondent of this research is the people who have an experience used three facial skin care product. The result show in facial skin care products, Ponds become the best facial skin care product chosen by respondent, from the six criteria price is the most important criteria for all among the alternatives. Price has important role in selecting facial skin care product. because price is the one of benchmark for the consumers to buy a product, when the price in Â offer is cheap and affordable it will be attract the consumer purchase intention.Keywords: consumer purchase decision, facial skin care products, analytical hierarchy process (AHP)Â